The utility of the ENTERORapid 24 kit for the identification of P. multocida and M. haemolytica - G. Tefera; J. Smola (Veterinární Medicína, 2002)
ENTERORapid 24 kit (PLIVA-Lachema, Czech Republic) was used for the identification of 321 strains isolated from the respiratory tract of different animal species in the CzechRepublic and Ethiopia. A total of 207 ( 64.5%) strains were identified at the species level within 4 to 8 hours of incubation. In the same way, 39 (12.1%) strains were successfully classified at the genus level. The remaining strains (23.4%) were not identified nor classified to the family Pasteurellaceae. On the other hand, the accuracy of the ENTERORapid 24 kit for the identification of P. multocida and M. haemoyltica was observed using 9 reference strains and the identification results were compaired with the results of the RapiD 20E kit (bioMérieux, France), which required an overall examination time of 4 hours. According to our observation, the ENTERO Rapid 24 kit is the fastest system forthe identification of P. multocida and M. haemolytica strains within 4 to 8 hours with a correct identification rate at thespecies level, with and without additional tests. For these reasons, we propose its modification for rapid identificaton of P. multocida, M. haemolytica and related bacterial species from the family Pasteurellaceae isolated from different animal species.